Pengaruh Kegiatan Kolase dengan Pemanfatan Bahan Alam terhadap Keterampilan Motorik Halus Anak di Taman Kanak-kanak Aisyiyah Koto Baru Maninjau Kabupaten Agam - Citra, Amelia; Wirman, Asdi (Darul Yasin Al Sys, 2024)
Early childhood education basically aims to support all aspects of child development. Teachers have various methods to stimulate children's fine motor development. One effective way is to utilise natural materials such as leaves, corals, stones, seeds and coconut pulp. These materials have the potential to be utilised in the creation of many artworks, encompassing collage techniques. The objective of this study was to eval_uate the influence of artistic activities involving natural materials on the refinement of children's fine motor skills at Aisyiyah Koto Maninjau Kindergarten in Agam Regency. The study employed a quantitative methodology utilising a pre-experimental design, specifically a one-group pretest-posttest strategy. The study showcased the efficacy of utilising natural materials in collage to enhance children's fine motor abilities. The post-test findings showed that collage using natural leaves was beneficial. The comprehensive study revealed an average N-Gain score of 7.87, which was categorised as high. The N-Gain percentage reached 78.7%, indicating a significant level of effectiveness. In conclusion, collage activities utilising natural materials proved effective in improving children's fine motor skills.